A dual‐band circularly polarized antenna with aid of dual cylindrical dielectric resonator blocks. Issue 4 (29th October 2018) - Gupta, Surbhi; Sharma, Anand; Das, Gourab; Gangwar, Ravi Kumar
Abstract: In this communication, a dielectric resonator based circularly polarized antenna is designed and investigated. A modified aperture is used to excite dual cylindrical dielectric resonator (CDR) blocks. Two important characteristics of the proposed radiator that makes it all the more attractive are as follows: (i) excitation of dual radiating modes that is, HEM11δ and TE01δ mode in cylindrical DR along with the support of dual‐band circularly polarized (CP) waves; (ii) arrangements of dual CDR blocks to reduce the Q‐factor which is useful to enhance the impedance bandwidth of both frequency bands. Fabrication as well as experimental measurement of the antenna prototype has been done for verifying simulation outcomes. This antenna design operates over dual frequency bands, that is, 5.01‐6.41 GHz and 7.3‐7.9 GHz with the fractional bandwidth of 24.73% and 9.39%, respectively. It supports CP waves over the frequency range 6.1‐6.5 GHz and 7.4‐7.8 GHz. The proposed antenna backs right‐hand circularly polarized (RHCP) radiation with an average gain of 4.5 dBi. These characteristics make it well fitted for WLAN, WiMAX (5.2/5.5/5.8 GHz), and downlink defense purpose satellite communication (7.2‐7.7 GHz).